2017
DOI: 10.18869/nirp.bcn.8.5.413
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Risk of Hearing Impairment Following the Cervical Spine Diseases by Measuring the Cervical Range of Movements: A Pilot Study

Abstract: Introduction:Cervical spine abnormalities can affect the ear vessels and or nerves with different mechanisms. Ear dysfunctions following cervical spine injuries can be manifested as hearing loss, vertigo, or tinnitus. Usually, cervical spine injuries can cause pain and Range of Motion (ROM) limitation. The major objective of this study was to determine which cervical ROM limitation was accompanied with higher level of hearing loss.Methods:In this cross-sectional study, 42 volunteers (20 women and 22 men) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…That means there is a relation between the left rotation limitation (LRL) and higher frequencies, related to sensory neural hearing loss. That is confirmed by Vasaghi-Gharamaleki, who found a significant difference between the mean hearing threshold of males with LRL and those without LRL [20]. It seems that vertigo and HL cannot be caused by the dysfunction in the lower neck (at segments lower than C3).…”
Section: Discussionmentioning
confidence: 63%
“…That means there is a relation between the left rotation limitation (LRL) and higher frequencies, related to sensory neural hearing loss. That is confirmed by Vasaghi-Gharamaleki, who found a significant difference between the mean hearing threshold of males with LRL and those without LRL [20]. It seems that vertigo and HL cannot be caused by the dysfunction in the lower neck (at segments lower than C3).…”
Section: Discussionmentioning
confidence: 63%
“…Similar study was conducted by Wendy Rheault chirrs byres et al (1992) where the purpose of the study was to investigate the Intertester reliability of the cervical range of motion device consisted of 22 subjects (15 female and 7 male) and they even concluded that the females were more prone to cervical dysfunction [13] Behnoosh vasghi-gharamaleki et al looked at the risk of hearing impairment following the cervical spinal disease by measuring the cervical range of movement with 53% of subjects had bilateral hearing loss, there was significant correlation was observed between hearing loss and ROM limitation of rotation to the left. [1] Melissa Ferranti et al In his study, a reported case from Germany a 36 year old soccer player hit his head with the ball and had sudden hearing loss in the right ear. After a single manipulation to the thoracic spine, the right sacroiliac joint and the right side neck (C 1 -C 4 ) his hearing immediately improved.…”
Section: Discussion:-mentioning
confidence: 99%
“…The upper neck or cervical consists of the occiput and the 1 st vertebrae. [1] The atlas vertebra i.e. C 1 has unique anatomy due to the absence of vertebral body & its ring like shape which makes it's different from other cervical vertebrae.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Tinnitus has previously been associated with cervical pathology 12 and cervical spine abnormalities can manifest itself as hearing loss, vertigo, or tinnitus [12][13][14] .…”
Section: Methodsmentioning
confidence: 99%